Mass Media and Political Disinformation in Indonesia - Basuki Agus Suparno; Susilastuti DN (The Indonesian Journal of Communication Studies, 2010)
This paper is the result of study that focus to media practices and disinformation especially to political disinformation in Indonesia. There are four factors that push this study so it was done seriously. First, information has the important role that can shape and color the reality. Second, freedom of information and expression require the accountable and transparency. Therefore it needs the responsibility for implementation. Third, information can be controlled by any kind of interests. Fourth, the spread of information can be limited, stored and deviated. The production and reproduction of information can be designed in according to any differences interests. Finally the gap to access of informationcanmakeitmisusingandmisleading. Inthiscontextmassmediahassignificantposition to make disinformation through selecting and drawing to the events in the line with the interests. Mass media can be controlled by the owner, parties, NGO (Non-Government Organization), and any factions that involve the competition. Then disinformation took place when communications conflict show up through giving false and mistaken information.